Management of Sales Promotion in Nepal: A Perspective on Construction-Material Market - Sthapit, Arhan; Bajracharya, Prabin (Administration and Management Review, 2010)
In view of the rising market for construction materials fuelled by spiral growth of urbanisation and resumption of infrastructure development works in the country; it is desirable to inquire into sales promotion strategies of the firms involved in manufacturing and marketing construction materials in general and reinforcement bars in particular. By researching into 232 buyers comprising construction contractors and individual builders, and another 150 retailers and dealers for two years (2006-2008), the study has sought to investigate into the current state of sales promotion programmes (SPPs) of construction material industries, which cater to the needs of a 30-billion rupees business of construction sector. The study has inferred that there is a noticeable influence of general SPPs, more specifically of money-based tools (cash rebates, discounts and cash coupons), on sales of reinforcement bars in the capital Valley's thriving market. The findings could prove instrumental to managers in formulating effective promotion strategies. Key words: Sales Promotion Programme (SPP); Integrated Marketing Communication (IMC); Construction Material Market (CMM); Reinforcement Bars (RBs) and Brands Administration And Management Review Volume 21, No. 2, 2009 Page: 1-21